Transformational leadership assessment in universities: A framework for institutional development - Nurlatifah, Siti; Komariah, Aan; Permana, Johar; Sururi, Sururi (Indonesian Research Journal in Education |IRJE|, 2025)
This study develops and validates a transformational leadership assessment framework specifically tailored to universities, with the aim of enhancing institutional development. A quantitative approach was used, with data collected from academic leaders and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The measurement model demonstrated strong reliability and validity, while the structural model showed explanatory power (R² = 1.000), with nine leadership dimensions fully predicting transformational leadership. Bootstrapping results confirmed the significance of all dimensions, with Individualized Consideration and Transformational Traits emerging as the strongest contributors. The findings highlight the multidimensional nature of transformational leadership and its significance in promoting innovation, digital readiness, collaboration, and organizational resilience in higher education. The study concludes by providing a validated framework for leadership development, evidence-based decision-making, and AI-supported evaluation systems, offering universities a tool to strengthen institutional capacity and sustainable growth.